The effects of ankle dorsiflexor fatigue on lower limb biomechanics during badminton forward forehand and backhand lunge - Tong, Jianhua; Lu, Zhenghui; Cen, Xuanzhen; Chen, Chaoyi; Ugbolue, Ukadike Chris; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Local muscle fatigue may have an adverse effect on the biomechanics of the lunge movement and athletic performance. This study analyzed the biomechanical indicators of the forward lunge in badminton players before and after fatigue of the ankle dorsiflexors. Methods: Using the isometric muscular strength testing system, 15 badminton players underwent an ankle dorsiflexor fatigue test. Before and after the fatigue experiment, five lunges were done in both the forehand forward (FH) and backhand forward (BH) directions, five in each direction. A Vicon motion capture system and an AMTI force measuring station were used to record lower limb kinematic and ground reaction force (GRF). Pre-fatigue and post-fatigue variability were determined using paired-samples t-tests, Wilcoxon signed rank test, and Statistical Non-parametric Mapping (SNPM). Result: The results showed that after fatigue, the peak angle of ankle dorsiflexion was significantly reduced (p = 0.034), the range of motion (ROM) of the ankle sagittal plane (p = 0.000) and peak angle of ankle plantarflexion (p = 0.001) was significantly increased after forehand landing. After fatigue, ankle inversion was significantly increased after forehand and backhand landings (FH: p = 0.033; BH: p = 0.015). After fatigue, peak knee flexion angles increased significantly (FH: Max: p = 0.000, Min: p = 0.000; BH: Max: p = 0.017, Min: p = 0.037) during forehand and backhand landings and ROM in knee flexion and extension increased (p = 0.009) during forehand landings. Knee inversion range of motion was significantly increased after fatigue (p = 0.024) during forehand landings. Peak hip flexion angle (p = 0.000) and range of motion (p = 0.000) were significantly reduced in forehand landings after fatigue. The mean loading rate (p = 0.005) and the maximum loading rate (p = 0.001) increased significantly during backhand landings after fatigue. Post-fatigue, the center of pressure (COP) frontal offset increased significantly (FH: p = 0.000; BH: p = 0.000) in the forehand and backhand landings. Conclusion: These results indicate that when the ankle dorsiflexors are fatigued, the performance of the forehand is significantly negatively affected, and the impact force of the backhand is greater.